Evolution of out-of-home food consumption in Brazil in 2008-2009 and 2017-2018 - Ilana Nogueira Bezerra; Thaís M Vasconcelos; Jessica Brito Cavalcante; Edna Massae Yokoo; Rosângela A Pereira; Rosely Sichieri (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE To describe the evolution of out-of-home food consumption in Brazil in 2008-2018. METHODS We used the 2008-2009 and 2017-2018 data from the Inquéritos Nacionais de Alimentação (INA - National Food Surveys), conducted amid 34,003 and 46,164 individuals, to estimate the frequency of out-of-home food consumption and the contribution of this consumption to specific foods. Food consumption was analyzed using food records in the 2008-2009 INA and 24-hour recalls in 2017-2018. Estimates were generated for Brazil in general, for urban and rural areas, for age groups (adolescent, adult, elderly), and for income bracket. RESULTS The frequency of out-of-home consumption decreased by 8.8% between the two surveys, with no change in the rural area, in the Northeast and South regions, and for the lowest income brackets. We observed a slight increase among the elderly and in the Midwest region. The contribution of out-of-home food consumption to daily energy intake also decreased (16.3% vs. 12.7%), excepting the rural area, where there was a reduction in the difference in relation to the urban area between the two surveys. For most items evaluated, the out-of-home food consumption decreased. The most consumed out-of-home food were alcoholic beverages, fried and baked snacks, soft drinks, pizza, sweets, and sandwiches in both surveys. CONCLUSION In 10 years, the prevalence of food consumption and the percentage of contribution of out-of-home food decreased in Brazil, but ultra-processed foods still figure as the most consumed food group outside the home.